2010
DOI: 10.1007/s00432-010-0871-2
|View full text |Cite
|
Sign up to set email alerts
|

Combined analysis of HPV DNA, p16, p21 and p53 to predict prognosis in patients with stage IV hypopharyngeal carcinoma

Abstract: PurposeWe examined p16, p21 and p53 expression in combination with the presence of human papillomavirus (HPV) DNA as molecular markers to predict survival in patients with stage IV hypopharyngeal squamous cell carcinoma (HSCC).MethodsParaffin-embedded tumours from HSCC patients (n = 75) were evaluated for p16, p21 and p53 expression by immunohistochemistry. HPV DNA was detected by GP5+/6+ consensus PCR and subsequent genotyping by E6/E7 type-specific PCR for HPV types 6, 11, 16, 18, 31, 33, 35, 39, 45, 51, 52,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
47
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 25 publications
4
47
1
Order By: Relevance
“…The majority of the studies in the meta-analysis differed from the study by Ernoux-Neufcoeur et al, which reported an 82% HPV prevalence, as only 9% of the tumours overexpressed p16, suggesting that, in that study, only a limited number of tumours truly had an active HPV infection (19,21).…”
Section: Hpv In Hypopharyngeal Cancermentioning
confidence: 67%
See 2 more Smart Citations
“…The majority of the studies in the meta-analysis differed from the study by Ernoux-Neufcoeur et al, which reported an 82% HPV prevalence, as only 9% of the tumours overexpressed p16, suggesting that, in that study, only a limited number of tumours truly had an active HPV infection (19,21).…”
Section: Hpv In Hypopharyngeal Cancermentioning
confidence: 67%
“…Other studies reported an HPV prevalence of 0-82%, with a recent meta-analysis showing an average of 21.9% (18)(19)(20)(21)(22)(23)(24)(25)(26)(27). The majority of the studies in the meta-analysis differed from the study by Ernoux-Neufcoeur et al, which reported an 82% HPV prevalence, as only 9% of the tumours overexpressed p16, suggesting that, in that study, only a limited number of tumours truly had an active HPV infection (19,21).…”
Section: Hpv In Hypopharyngeal Cancermentioning
confidence: 68%
See 1 more Smart Citation
“…The aim of this study was to determine the prevalence of human papillomavirus (HPV) in patients with laryngeal benign lesions (LBLs) and laryngeal squamous cell carcinomas (LSCCs) using a sensitive E6/E7 type-specific PCR. Paraffinembedded samples from LBL (n=39) and LSCC patients (n=67) were evaluated for the presence of HPV DNA by GP5 + /GP6 + consensus PCR and E6/E7 type-specific PCR for HPV types 6,11,16,18,31,33,35, 39, 45, 51, 52, 53, 56, 58, 59, 66 and 68. In LSCCs, immunohistochemical staining of p16, p53 and EGFR was also assessed.…”
mentioning
confidence: 99%
“…Among the types of this virus that have been identified, more than 80 have been characterized, and 40 types are able to infect the anogenital area (3) . The identification of HPV types is currently being applied in clinical practice as a prognostic predictor of cervical cancer in infected women (4) .…”
Section: Introductionmentioning
confidence: 99%